On the Eocene age of Limodromus Motschulsky, 1850, with description of L. hoffeinsorum sp. n. from Baltic Amber (Coleoptera: Carabidae: Platynini) - Schmidt, Joachim (Zootaxa, 2015)
The first platynine ground beetle, Limodromus hoffeinsorum sp. n., is described from Baltic amber at species level. The fossil species is considered the sister taxon of the modern species group of L. assimilis (Paykull, 1790). However, it was adapted to warmer climate conditions. The habitat of the new species is assumed similar to that of the modern L. klausnitzeri Schmidt, 2005, which represents a more basal branch of Limodromus and which occurs in the mountains of northern Vietnam.